The experience of talking about hearing voices with family, friends, and others. Issue 1 (2nd January 2020) - Watkins, Simon; Gupta, Anjula; Sanderson, Chris
ABSTRACT: Objective : There is evidence to suggest that close social networks and wider social influences have a significant impact on people who hear voices. The aim of this research was to explore people's experiences of talking about voice hearing with family, friends, and others. Method : Transcribed interviews with five participants, recruited through mental health services, were analysed using Interpretative Phenomenological Analysis (IPA). Results : Two superordinate themes, each with multiple subordinate themes, were developed from the interviews: "Who can I talk to about this ?", which explores the way people communicate carefully about their voices to manage their experiences of shame, and "I was shocked by how they responded", which considers others' reactions to participants disclosures and the impact this had on the participants. Conclusions : The research findings are compared to the existing literature, limitations of the research are considered, and clinical considerations for supporting people who hear voices are explored.